2006
DOI: 10.1007/s11095-006-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

CYP Induction-Mediated Drug Interactions: in Vitro Assessment and Clinical Implications

Abstract: Cytochrome P450 (CYP) induction-mediated interaction is one of the major concerns in clinical practice and for the pharmaceutical industry. There are two major issues associated with CYP induction: a reduction in therapeutic efficacy of comedications and an induction in reactive metabolite-induced toxicity. Because CYP induction is a metabolic liability in drug therapy, it is highly desirable to develop new drug candidates that are not potent CYP inducer to avoid the potential of CYP induction-mediated drug in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
185
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(189 citation statements)
references
References 217 publications
(250 reference statements)
4
185
0
Order By: Relevance
“…The drug-induced expression of the CYP3A4 gene in the liver, and to a lesser extent in the intestine, is predominantly regulated through PXR [15]. In contrast, VDR controls CYP3A4 transactivation by the secondary bile acid lithocholic acid (LCA) and subsequent biotransformation of LCA in the intestine [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The drug-induced expression of the CYP3A4 gene in the liver, and to a lesser extent in the intestine, is predominantly regulated through PXR [15]. In contrast, VDR controls CYP3A4 transactivation by the secondary bile acid lithocholic acid (LCA) and subsequent biotransformation of LCA in the intestine [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It catalyzes the metabolism of more than 50% of clinically used drugs (Schuetz, 2004). Induction of CYP3A4 can result in clinically significant drug-drug interactions or autoinduction (Lin, 2006) and, therefore, is a major concern for the pharmaceutical industry.…”
mentioning
confidence: 99%
“…Several studies have reported induction by DMSO of several P450s, especially the CYP3A subfamily, in both primary hepatocytes (LeCluyse et al, 2000;Su and Waxman, 2004;Lin, 2006) and hepatoma cell lines (Aninat et al, 2006). Although most effects were obtained with a 2% DMSO concentration, some increase was also seen with concentrations as low as 0.1% in primary human hepatocytes (LeCluyse et al, 2000).…”
Section: Downloaded Frommentioning
confidence: 99%